La ética en la agricultura para el cuidado del medio ambiente en el Ecuador - Saavedra Mera, Karina Auxiliadora (Editorial Grupo AEA, 2022)
The global challenges we face are the increasing scarcity and depletion of natural resources, at a time of growing demand for food, goods and services; agriculture, including crops, livestock, forestry, fisheries and aquaculture, are growing rapidly. Ecuador has one of the highest rates of biodiversity per square meter on the planet, livestock and agriculture are no strangers to this classification. Modern industrial agriculture, which is characterized by the biotechnology model, must be exposed to sustainable agriculture. The objective of the research is to analyze how ethics influences within the field of agriculture to provide environmental care in Ecuador, as well as to achieve sustainability of life on the planet. This project is based on a qualitative explanatory methodology with the use of a bibliographic review of different scientific journals through the evaluation and search of information. When analyzing the results, it can be seen that international trade has very low controls and certifications, putting at risk the ecological production in order to generate low production costs by making excessive use of land, water and genetic resources, endangering not only Ecuador, but the world in general. Finally, it is concluded that ethics linked to agriculture strengthens a measure of long-term care of the planet in which we live, by taking care of it, we also take care of the inhabitants.